A bacterial strain of pseudomonas aeroginosa B0406 pathogen opportunistic,prduce a biosurfactant with tolerance to changes of pH, salinity and temperature. - Somoza Coutino, Gilberto (2019)
A bacterial strain of pseudomonas aeroginosa B0406 pathogen opportunistic,prduce a biosurfactant with tolerance to changes of pH, salinity and temperature.